Pemasangan Solar Panel pada Industri Rumah Tangga UMKM di Kota Bogor untuk Mensuplai Listrik pada Produksi Lampu LED - Yusuf, Arba'i; Haryanti, Munnik (Jurnal Pengabdian Rekayasa dan Wirausaha, 2024)
In general, UMKM industries in Bogor city utilize PLN electricity to run their operations.In the city of Bogor there is an industry of service and production of led lights that always use electricity in every activity.The implementation of this community service activity is to supply electricity to the industry of service and led lamp production in UMKM in the Bogor city area.The process of community service activities begins with a site survey of UMKM industry players.Furthermore, coordination is carried out with the campus, lecturers and students, donators, and owners or managers of business places.Then make a cost budget plan (RAB) and purchase materials, check the entire system and install the equipment at the location of the UMKM business place and end with the handover process.The installation of this solar panel has been able to supply several equipment used by UMKM players, namely laptops, wifi modems, production equipment, and several lighting lamps, where the total power required is 305W.The target of this activity is for people who have small businesses that have a turnover of less than 500 million per year.The installation of solar panels for the UMKM industry, namely the service and production of led lights in the city of Bogor, has helped reduce the cost of electricity bills so that the profits from this industry can be diverted to increase production and increase income for the owners of these UMKMs.